CD8-positive mycosis fungoides masquerading as pyoderma gangrenosum - Maitrayee Saha; Bhawna Bhutoria Jain; Sarbani Chattopadhyay; Indrashis Podder (Wolters Kluwer Medknow Publications, 2016)
Mycosis fungoides (MF), a primary cutaneous T-cell lymphoma, accounts for <1% of non-Hodgkin lymphomas. The diagnosis of classic MF is based on a constellation of typical clinical presentation, histopathology, immunohistochemistry, and T-cell monoclonality detected by molecular studies. Rarely, atypical clinical presentation may occur. The typical immunohistochemical phenotype is, CD2 +ve, CD3 +ve, CD5 +ve, CD4 +ve, and CD8 − ve. Here, we report a rare case of CD8 +ve MF in a 43-year-male patient who was clinically diagnosed as pyoderma gangrenosum initially. The atypical presentation and rarity of such case have prompted this report.